Effectiveness of Nurse-Led Spiritual Interventions in Cardiovascular Care: A Systematic Review of Psychological, Spiritual, and Quality of Life Outcomes - Safri (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
Cardiovascular diseases (CVDs) impact not only physical health but also psychological and spiritual well-being, affecting patient recovery and outcomes. This systematic review aimed to identify and evaluate the effectiveness of nurse-led spiritual interventions in improving psychological and spiritual outcomes among patients with cardiovascular disease. A literature search was conducted across PubMed, CINAHL, Scopus, and ScienceDirect for studies published between 2014 and 2025, including RCTs, quasi-experimental, and qualitative designs involving adult cardiovascular patients. Outcomes of interest were anxiety, depression, spiritual well-being, resilience, and quality of life. Nineteen studies were included: eight RCTs, ten quasi-experimental, and one qualitative study. Interventions were categorized into four types: Islamic-based spiritual therapy, structured counselling and education, technology-assisted programs, and experiential models. Most studies demonstrated significant improvements in anxiety, depression, spiritual well-being, and life satisfaction. The qualitative study emphasized practical spiritual care strategies, such as distraction techniques and involving family. Nurse-led spiritual interventions are effective, especially in culturally religious contexts, and their integration into routine nursing care is strongly recommended. Further research should assess their long-term effectiveness and explore how these interventions can be adapted to secular or diverse cultural settings to support holistic, patient-centered care.